Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO